Pengaruh Model Pembelajaran Word Square terhadap Hasil Belajar Fisika - Junaidi Junaidi; Tri Ariani; Wahyu Arini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to see how the effect of the word square learning model on student physics learning outcomes. The population in this study were all Grade VII students of SMPIT AN-NIDA 'Lubuklinggau, which numbered 52 people. Therefore, researchers trying to use this type of research are experiments using Pretest-Posttest Control Group Design. Data collection techniques used were essay-shaped test techniques as many as 5 questions. The final test score data were analyzed using the z-test. Based on the results of data analysis zcount = 2.44 and ztabel = 1.68 because zcount> ztable, then the conclusions obtained are the effect of Word Square learning model on student learning outcomes. Keywords: Word Square, Physics Learning Outcomes.